A “mulher do futuro” em periódicos brasileiros: vestuário e decoração como tecnologias de gênero (1960 e 70) - Bostelmann, Pamela (2017)
The imagery mobilized by the space race in the second post-war period instigated the creation of a visual repertory that soon became the source of inspiration in several fields of cultural production. In this work I aim to discuss the construction of the "woman of the future" figure through the articulation between the productions affiliated to this imaginary in clothing and interior decoration. The study covers the 1960s and 1970s and is centered on the representations of domestic interiors published by Casa & Jardim magazine and the editorials and advertisements for clothing published by magazines Claudia and Manequim. These publications put into circulation a series of imagery and textual resources that demonstrated aspects of the time’s social behavior, serving as basis for the investigation of the new representations of femininities which appeared in that period. The choice to focus on the articulation between interior decoration and clothing is based on the historically constructed relation between these materialities and the female body, therefore being an important part in the construction of gender, class and generation identities. With this work I intend to show that the materialities of domestic interiors and clothing inspired by the space age iconography acted as devices that created and reinforced notions of femininity.